Modifikasi Kunci Algoritma IDEA Menggunakan Random Key Midsquare Pada Citra - Fuady Mahbub; Muhammad Syahrizal; Rivalri K. Hondro (STMIK Budi Darma, 2020)
A Digital Image may have important information in it where this confidential information should not be seen by unauthorized people. Information in a digital image can be easily remembered by others compared to information in the form of text. For this reason, an image containing information must be encrypted using cryptography, but encoding the image is of course not enough to protect the information contained in it because of the key that may be known by outsiders. To maintain the confidentiality of the information from the image, previously the image will be encoded using the IDEA algorithm, however, the security level of the algorithm should be further improved. Therefore, to improve the quality of digital image security, the IDEA algorithm key is first modified using a Midsquare random number generator. Through the process of the IDEA algorithm which is quite complicated, coupled with the previously modified keys using the Random Key Midsquare random number generator, it is expected to be able to improve the security quality of confidential information encoded in a digital image, so that the information contained in the digital image does not leak to parties. who are not responsible.Keywords: Image, Cryptography, IDEA, Random Key Midsquare